PENGARUH RETURN ON EQUITY, ECONOMIC VALUE ADDED, DAN DIVIDEND PAYOUT RATIO TERHADAP HARGA SAHAM PERUSAHAAN MANUFAKTURDI BURSA EFEK INDONESIA PERIODE 2020-2022 - Vadana , Abhi; Kusumawati, Synthia Madya (BALANCE: Jurnal Akuntansi, Auditing dan Keuangan, 2025)
This study aims to analyze the influence of Return on Equity (ROE), Economic Value Added (EVA), and Dividend Payout Ratio on the stock prices of manufacturing companies listed on the IDX during the period 2020-2022. The sample selection was conducted using the purposive sampling method, resulting in a total of 101 samples. Data analysis was conducted using normality tests, multiple linear regression analysis, and classical assumption tests processed with SPSS software. The research results show that ROE has a positive and significant effect on stock prices, which means that an increase in ROE affects an increase in stock prices. EVA was also found to have a positive and significant impact on stock prices, indicating that companies capable of creating economic value added tend to have higher stock prices. On the contrary, DPR shows a negative and significant influence on stock prices, indicating that high dividend payments might be perceived negatively by investors.